0274 The profile of informal carers in a cohort of 50–64 year-olds: results from the health and employment after fifty (heaf) study. (21st August 2017) - Harris, E Clare; D'Angelo, Stefania; Syddall, Holly; Linaker, Cathy; Coggon, David; Walker-Bone, Karen; Palmer, Keith T
Abstract : Background: With increases in the UK pensionable age, people are now expected to work to older ages, but they may also have caring responsibilities which constrain their capacity to work and could affect their health. To explore the extent of the problem, we assessed the profile of unpaid carers in the HEAF study. Methods: 8134 men and women aged 50–64 were recruited from 24 English general practices. Socio-demographic, lifestyle and health characteristics were elicited by postal questionnaire, along with weekly hours giving personal care to someone in the home or family. Results: 644 (17.4%) men and 1153 (26.0%) women had caring responsibilities; of these, 93 (14%) and 199 (17%) reported caring for ≥20 hours/week respectively. Participants with low levels of education or social class, non-homeowners, and those struggling to manage financially were more likely to be carers. Carers of both sexes were less likely to be working and, if working, more likely to be part-time or often working shifts. Carers, and particularly those caring for ≥20 hours/week, reported worse health (self-rated, depression and sleep problems). Prevalence of chronic musculoskeletal pain was 32% and 44% respectively among men and women who cared ≥20 hours/week, in comparison with 25% and 27% amongst non-carers. Conclusions: The requirement to be a carer is common in the HEAF cohort. Those affected are less likely to be in full-time employment and more likely to be in worse health. There is a need for further research on how older workers with caring responsibilities can be better supported.